Ongoing Efforts to Improve Antimicrobial Utilization in Hospitals among African Countries and Implications for the Future - Zikria Saleem; Brian Godman; Aislinn Cook; Muhammad Arslan Khan; Stephen M. Campbell; Ronald Andrew Seaton; Linda Siachalinga; Abdul Haseeb; Afreenish Amir; Amanj Kurdi; Julius C. Mwita; Israel Abebrese Sefah; et al. (MDPI AG, 2022)
There are serious concerns with rising antimicrobial resistance (AMR) across countries increasing morbidity, mortality and costs. These concerns have resulted in a plethora of initiatives globally and nationally including national action plans (NAPs) to reduce AMR. Africa is no exception, especially with the highest rates of AMR globally. Key activities in NAPs include gaining a greater understanding of current antimicrobial utilization patterns through point prevalence surveys (PPS) and subsequently instigating antimicrobial stewardship programs (ASPs). Consequently, there is a need to comprehensively document current utilization patterns among hospitals across Africa coupled with ASP studies. In total, 33 PPS studies ranging from single up to 18 hospitals were documented from a narrative review with typically over 50% of in-patients prescribed antimicrobials, up to 97.6% in Nigeria. The penicillins, ceftriaxone and metronidazole, were the most prescribed antibiotics. Appreciable extended prescribing of antibiotics up to 6 days or more post-operatively was seen across Africa to prevent surgical site infections. At least 19 ASPs have been instigated across Africa in recent years to improve future prescribing utilizing a range of prescribing indicators. The various findings resulted in a range of suggested activities that key stakeholders, including governments and healthcare professionals, should undertake in the short, medium and long term to improve future antimicrobial prescribing and reduce AMR across Africa.